Consumer Perception Through Healthy Drinks Packaging Design - Feizal, Affan Abdul Ghaffur; Aldianto, Leo (Journal of Business and Management, 2012)
Healthy living is already become concern in today’s society. According to many studies, people are also increasingly reflective in matters of health and willing to adopt health oriented changes in their eating habits. This change of habits creates a new opportunity in food and drinks industry especially for healthy drinks products. The intense competition between healthy drinks products made consumers is faced with large number of choices. It will be better for the producers to know consumers perceptions toward healthy drinks packaging design to overcome the competitions. The objective of this study is to find out on how consumer perception towards healthy drinks packaging design.In doing this research, Consumer Perceived Value (CPV) theory by Sweeney and Soutar (2000) is used. Basically there are 4 dimension of CPV; Emotional value, Social value, Quality/performance value, Price/value for money. But this research only used the third value which is the Quality/performance value because this research only covers with the consumer’s perception and consumer perceived value of the function of the products. The information processing model also used to understand how consumers build the perceptions.Men and women aged 15-40 years old who live in Bandung was taken as a respondent in this research. The selection of this range of ages is expected to get more variation in the result. By using a judgmental approach, questionnaires have been distributed between 29th July – 8th August 2012 to men and women who concern about health. Three isotonic drinks products were selected as research object. There are five element of packaging, which measured in each product by Likert scale. They are Logo, Image and Other Graphical Elements, Color, Size and Shape, and Benefits. There are also four attribute of perceived value measured; Product Quality Consistency, Product is well made, Product Has an Acceptable Standard of Quality, and the product will last for long time. Found in the analysis, Pocari Sweat successfully become a good example for healthy drinks packaging design, since it draws the highest score for each elements among the products. Pocari Sweat was success in the three level of information processing. It succeeds in implementing the same ambiance from advertisement to the product packaging. Also found that simple logo is more capable to bring the healthiness impression. Using bright color can help to emphasize the healthiness value. Besides, it also can make other important attribute can stand out. The clear visibility of the bottle became important for consumers to see the water inside the bottle.Keywords: Consumer Perception, Product Design, Perceived Value.Category: Marketing; Decision-makin